Manipulation of Intraday Durations of Blue- and Red-Light Irradiation to Improve Cos Lettuce Growth - Jishi, Tomohiro; Matsuda, Ryo; Fujiwara, Kazuhiro (Frontiers in Plant Science, 2021)
The morphology of plants growing under combined blue- and red-light irradiation is affected by the presence or absence of time slots of blue- and red-light mono-irradiation. The purposes of this study were to investigate the morphology and growth of cos lettuce grown under light irradiation combining several durations of blue- and red-light simultaneously and independent mono-irradiations of blue and red light during the day, and to clarify the effects of the durations of blue-light mono-irradiation and blue-light irradiation. Young cos lettuce seedlings were grown under 24-h blue-light irradiation with a photosynthetic photon flux density (PPFD) of 110 µmol m−2 s−1 (B+0R) or under 24-h blue-light irradiation with a PPFD of 100 µmol m−2 s−1 supplemented with 8-h (B+8R), 16-h (B+16R), and 24-h (B+24R) red-light irradiation with PPFDs of 30, 15, and 10 µmol m−2 s−1, respectively (Experiment 1). The daily light integral was 9.50 mol m−2 in all treatments. In Experiment 1, leaf elongation was promoted as the duration of red-light irradiation decreased and the duration of blue-light mono-irradiation increased. The maximum shoot dry weight was observed under the B+8R treatment. Growth was likely promoted by the expansion of the light-receptive area caused by moderate leaf elongation without tilting. In Experiment 2, young cos lettuce seedlings were grown as for Experiment 1, but blue- and red-light irradiation intensities were reversed (R+0B, R+8B, R+16B, and R+24B). Leaf elongation was promoted by the absence of blue-light irradiation (R+0B). The leaf surface was increasingly flattened, and the shoot dry weight was enhanced, as the duration of blue-light irradiation increased. Thus, cos lettuce leaf morphology may be manipulated by adjusting each duration of blue-light mono-irradiation, red-light mono-irradiation, and blue- and red-light simultaneous irradiation, which can, in turn, promote cos lettuce growth.